SPD-Parteitag 1970 in Saarbrücken; 11.05.1970 - 14.05.1970 (2010)
3. Verhandlungstag am 13.05.1970:<NZ>Fortsetzung Aussprache zum Referat von Willy Brandt:<NZ>Uwe Rüth, Protokoll Seiten 484 - 487, 00'01'' - 08'08'';<NZ>Antje Huber, Protokoll Seiten 487 - 488, 08'09'' - 09'00'';<NZ>Richard Bünemann, Protokoll Seite 488, 09'02'' - 10'46'';<NZ>Peter Glotz, Protokoll Seiten 488 - 492, 11'02'' - 18'46'';<NZ>Hans Eichel, Protokoll Seiten 492 - 496, 19'11'' - 28'04'';